Animal models for cystic fibrosis: A systematic search and mapping review of the literature – Part 1: genetic models. (August 2020) - Leenaars, Cathalijn HC; De Vries, Rob BM; Heming, Anna; Visser, Damian; Holthaus, David; Reijmer, Joey; Elzinga, Janneke; Kempkes, Rosalie WM; Punt, Carine; Beumer, Wouter; Meijboom, Franck LB; Ritskes-Hoitinga, Merel
Animal models for cystic fibrosis (CF) have enhanced our understanding of the pathology and contributed to the development of new treatments. In the field of CF, many animal models have been developed and described. To our knowledge, thus far, none of the reviews of CF animal models has used a systematic methodology. A systematic approach to creating model overviews can lead to an objective, evidence-based choice of an animal model for new research questions. We searched Pubmed and Embase for the currently available animal models for CF. Two independent reviewers screened the results. We included all primary studies describing an animal model for CF. After duplicate removal, 12, 304 publications were left. Because of the large number of models, in the current paper, only the genetic models are presented. A total of 636 publications were identified describing genetic animal models for CF in mice, pigs, ferrets, rats and zebrafish. Most of these models have an altered Cftr gene. An overview of basic model characteristics and outcome measures for these genetic models is provided, together with advice on using these data. As far as the authors are aware, this is one of the largest systematic mapping reviews on genetic animal models for CF. It can aid in selecting a suitable model and outcome measures. In general, the reporting quality of the included publications was poor. Further systematic reviews are warranted to determine the quality and translational value of these models further.